2005
DOI: 10.1007/s00221-005-0073-3
|View full text |Cite
|
Sign up to set email alerts
|

Control of aperture closure during reach-to-grasp movements in parkinson’s disease

Abstract: This study examined whether the pattern of coordination between arm-reaching toward an object (hand transport) and the initiation of aperture closure for grasping is different between PD patients and healthy individuals, and whether that pattern is affected by the necessity to quickly adjust the reach-to-grasp movement in response to an unexpected shift of target location. Subjects reached for and grasped a vertical dowel, the location of which was indicated by illuminating one of the three dowels placed on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
23
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 55 publications
7
23
1
Order By: Relevance
“…Furthermore, it appears that the same model can accurately describe the control law employed by all participating subjects. These results are fully consistent with data from our previous study in which we found that the control law related to grasp initiation is similar even between healthy controls and Parkinson patients (Rand et al 2006). Thus, the state of arm reach (velocity and acceleration) and state of grasp (aperture amplitude) are likely taken into account by the CNS in order to control the initiation of the aperture closure.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, it appears that the same model can accurately describe the control law employed by all participating subjects. These results are fully consistent with data from our previous study in which we found that the control law related to grasp initiation is similar even between healthy controls and Parkinson patients (Rand et al 2006). Thus, the state of arm reach (velocity and acceleration) and state of grasp (aperture amplitude) are likely taken into account by the CNS in order to control the initiation of the aperture closure.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, we used it to elucidate the relationship between arm movement parameters and a decision to initiate aperture closure. The existence of such a control law has been shown also in our previous study (Rand et al 2006). This study demonstrates that the aperture closure distance significantly increases with faster transport speed across a range of speed conditions.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…For reach-to-grasp movements in PD patients a slowing of hand transport and a discoordination between hand transport and grasp formation with a pronounced delay of the onset of the grasp opening has been documented [8][9][10]21]. Interestingly, we found that STN-DBS shortened the time of peak grasp aperture in relation to the time of hand transport and thus normalized the temporal coupling between the reach and grasp components of the reach-to-grasp task in PD.…”
Section: Discussionsupporting
confidence: 59%
“…The subtest dexterity measures coordinated and independent finger movements and requires skills for grasping and holding the pins and putting them into an intended target. As mentioned in the introduction, PD patients already have difficulties in movement initiation to the target [11] and in the coordination of fine motor function of the moving hand [12,31,32]. Plotnik et al [33] reported that PD patients and elderly subjects responded substantially slower to a required movement modification than to the initial movement required.…”
Section: Discussionmentioning
confidence: 99%